Harut and Marut - Margoliouth, D. S. (The Muslim world, 1928)
And when there came to them (the Jews) an Apostle from Allah confirming what was in their possession, a section of those who had been given the Book flung the Book of Allah behind their backs, as though they knew not; (96) and followed what the demons recited over the kingdom of Solomon, and Solomon did not disbelieve, but the demons disbelieved, teaching men sorcery, and what was revealed to the two angels (or kings) in Babylon, Harut and Marut, and they twain taught no one until they said, We are only a probation, and disbelieve thou not; and they would learn from them twain that whereby they would separate between a man and his wife, and they harm no one thereby save by permission of Allah, and they learn what harms them and profits them not, and verily they know that whoso purchaseth it hath no share in the latter world.